Evaluating the Effects of Startup Soybean Meal on Nursery Pig Growth Performance, Fecal Dry Matter, and Apparent Total Tract Digestibility of Crude Protein - Paula Giacomini; Katelyn N. Gaffield; Mike D. Tokach; Joel M. DeRouchey; Robert D. Goodband; Jason C. Woodworth; Jordan T. Gebhardt; Hari B. Krishnan (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 300 pigs (241 × 600, DNA; initially 11.8 ± 0.01 lb) were used in a 38-d growth study. Pens were randomly allotted to one of five dietary treatments in a generalized randomized complete block design with five pigs per pen and 12 replicate pens per treatment. Two batches of soybean meal were sourced from the same processing plant. The first batch was obtained from the initial truckload from the startup phase of the plant. Approximately four hours later, a second batch was sourced when the soybean meal processing had stabilized. To assess the nutritional quality of soybean meal, protein solubility in potassium hydroxide (KOH) and trypsin inhibitor units (TIU) were measured on both sources. The startup soybean meal had a KOH solubility of 68.9% and a TIU of 6.34 ± 0.12 TIU/mg seed powder, while the normal soybean meal had a KOH solubility of 82.1% and a TIU of 7.12 ± 0.54 TIU/mg seed powder. The two different soybean meal sources were blended to create a titration of startup soybean meal in the diet. Startup soybean meal replaced 0, 25, 50, 75, and 100% of the normal soybean meal to form the dietary treatments. The nutritional composition of both soybean meal sources was considered the same and thus the startup soybean meal replaced the normal soybean meal on an equal weight basis without other changes to the formulation. All diets were provided in mash form, with dietary treatments fed throughout all three dietary phases. From d 0 to 10, increasing the startup soybean meal led to a marginal decrease (linear, P < 0.10) in ADG and d 10 BW and poorer (linear, P = 0.041) F/G. From d 10 to 22, increasing startup soybean meal decreased ADG and d 22 BW (linear, P < 0.05), with a marginal worsening (linear, P = 0.067) of F/G. However, no differences were observed for any growth performance criteria from d 22 to 38 and for the overall nursery period. On d 10 and 22, fecal DM decreased (d 10, linear, P = 0.053; d 22, linear, P = 0.045) as startup soybean meal increased in the diet. The apparent total tract digestibility (ATTD) of DM tended to decrease (linear, P = 0.095) as startup soybean meal increased in the diet, but there was no evidence of a difference in ATTD of CP. In conclusion, the quality of startup soybean meal can affect the performance of nursery pigs, specifically during the first three weeks after weaning, suggesting that pigs may be particularly sensitive to soybean meal quality during that phase of growth. However, pigs adjusted to the startup soybean meal toward the end of the nursery period, leading to no differences in overall growth.
Keywords: anti-nutritional factors; nursery; protein solubility; soybean meal; swine